2013
DOI: 10.7897/2230-8407.04637
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Free Radical Scavenging Activity of Two Main Varieties of Cicer Arietinum Sprouts

Abstract: The purpose of the study was to evaluate the extent of free radical scavenging properties and antioxidant effects of crude extracts of sprouted Cicer arietinum (Chick pea/Chana/Bengal gram) seeds. Two main varieties of Cicer arietinum seeds viz. Kabuli-chana (cream seed-coat) and Bengal gram (brown seed-coat) were examined and compared for their free radical scavenging properties and antioxidant effects. A crude methanol extract of the sprouted seeds were prepared. Free radical scavenging properties were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results showed that the two Cicer arietinum extracts were differed in their capacities to quench or inhibit DPPH, hydrogen peroxide and lipid peroxide. Brown colored Cicer arietinum sprouts showed the greatest activity against DPPH radicals, hydrogen peroxide radicals and lipid peroxide compared to the cream variety [45][46].…”
Section: Cicer Arietinummentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the two Cicer arietinum extracts were differed in their capacities to quench or inhibit DPPH, hydrogen peroxide and lipid peroxide. Brown colored Cicer arietinum sprouts showed the greatest activity against DPPH radicals, hydrogen peroxide radicals and lipid peroxide compared to the cream variety [45][46].…”
Section: Cicer Arietinummentioning
confidence: 99%
“…The results showed that the two Cicer arietinum extracts were differed in their capacities to quench or inhibit DPPH, hydrogen peroxide and lipid peroxide. Brown colored Cicer arietinum sprouts showed the greatest activity against DPPH radicals, hydrogen peroxide radicals and lipid peroxide compared to the cream variety [45][46].The root of Cicer arietinum was extracted using solvents of different polarities and explored for in vitro free radical scavenging activity. Preliminary assays of three different extracts of Cicer arietinum root showed that the extracts possess electron donating ability and reduction of ferric ion to ferrous in a cell free system at pH-7.4.…”
mentioning
confidence: 99%